2022
DOI: 10.1126/sciadv.abm8757
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of gene evolution generating mucin function

Abstract: How novel gene functions evolve is a fundamental question in biology. Mucin proteins, a functionally but not evolutionarily defined group of proteins, allow the study of convergent evolution of gene function. By analyzing the genomic variation of mucins across a wide range of mammalian genomes, we propose that exonic repeats and their copy number variation contribute substantially to the de novo evolution of new gene functions. By integrating bioinformatic, phylogenetic, proteomic, and immunohistochemical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…SMR3A and SMR3B, along with PROL1 (also named OPRPN), comprise a group of salivary SCPP genes that code for proteins rich in proline and have a distinct phylogenetic history. We previously showed that these proteins, due to their richness in proline, have served as precursors for the de novo evolution of mucin function at various stages of the mammalian phylogeny [13]. Our current analysis confirmed that based on nucleotide sequence homology, SMR3A and SMR3B likely originated as duplicates of PROL1 [34].…”
Section: Varied Origins Of Saliva-related Scpp Genes In Primatessupporting
confidence: 82%
“…SMR3A and SMR3B, along with PROL1 (also named OPRPN), comprise a group of salivary SCPP genes that code for proteins rich in proline and have a distinct phylogenetic history. We previously showed that these proteins, due to their richness in proline, have served as precursors for the de novo evolution of mucin function at various stages of the mammalian phylogeny [13]. Our current analysis confirmed that based on nucleotide sequence homology, SMR3A and SMR3B likely originated as duplicates of PROL1 [34].…”
Section: Varied Origins Of Saliva-related Scpp Genes In Primatessupporting
confidence: 82%
“…Perhaps the largest knowledge gap in why the Denisovan-like haplotype of MUC19 would be under positive selection is determining its underlying function. Mucins are secreted glycoproteins responsible for the gel-like properties and the viscosity of the mucus [Pajic et al, 2022]. MUC19 is associated with gland function in humans, which can be important components of immune response, in particular its role in mucus formation in tracheal submucosal glands in preventing pathogenic infections [Chen et al, 2004; Zhu et al, 2011; Reynolds et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…A membrane-associated protein with a high level of glycosylation, Mucin, forms the backbone of mucus, covering the apical surface of epithelial cells in higher animals. Its functions are not limited to barrier function: mucins are able to regulate cell behavior and interactions 38,39 . The enzymes procollagen lysine hydroxylase, glycosyltransferase and peroxidasin have also been found to provide post-translational modifications of collagens (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…A membrane-associated protein with a high level of glycosylation, Mucin, forms the backbone of mucus, covering the apical surface of epithelial cells in higher animals. Its functions are not limited to barrier function: mucins are able to regulate cell behavior and interactions 38,39 .…”
Section: Extracellular Matrix Genes Analysismentioning
confidence: 99%